Tips and tricks for laparoscopic cholecystectomy in the patient with ventriculoperitoneal shunt; a case report - Carmen Popa; Andrei Moisin; Mihai Faur; Mihaela Racheriu; Ramona Coca; Cristian Mihai Branescu; Tiberiu Trotea; Denisa Tănăsescu (Journal of Mind and Medical Sciences)
Laparoscopic surgery in patients with ventriculo-peritoneal shunt is challenging in terms of technical approach. The severity of possible complications and the lack of studies on this association increase the surgeon's discomfort with such surgery. The main complications that may occur are increased intracranial pressure, secondary pneumo-peritoneum pneumocephalus, encephalitis and the risk of catheter injury during laparoscopic procedures. We present the case of a 56-year-old patient operated in 2004 for a basilar artery top aneurysm with subarachnoid hemorrhage and secondary hydrocephalus, for which a ventriculo- peritoneal shunt was fitted. This patient presented in our clinic with diffuse abdominal pain, more accentuated in the right hypochondrium, nausea, postprandial biliary vomiting, inappetence, asthenia, fatigability, symptoms with onset about 6 months, but accentuated in the last 48 hours. The patient underwent surgery and the evolution was favorable, being discharged without postoperative complications.